Pete Seeger [videorecording (DVD)] : the power of song - Brown, Jim, 1950-; Seeger, Pete, 1919-2014 (Miriam collection, 2008)
A look at the life of controversial musician, activist, and environmentalist Pete Seeger, and how he used his songs to promote social change. Includes archival footage and interviews with Bob Dylan, Bruce Springsteen, Joan Baez, Arlo Guthrie, and more.